2021
DOI: 10.3390/ijerph18157772
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Shape People’s Attitudes towards the COVID-19 Pandemic in Germany—The Influence of MEDIA, Politics and Personal Characteristics

Abstract: Misinformation that accompanied the current SARS-CoV-2 pandemic led to an impaired risk perception, resulting in the refusal of personal protection measures, as well as a reduced willingness to receive a vaccination. In order to identify factors that might influence people’s attitudes towards COVID-19 policies and engagement in mitigation measures, we carried out a cross-sectional study in Germany. Altogether, n = 808 participants completed our questionnaire concerning items on demographics, media consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
2
23
1
6
Order By: Relevance
“…The risk of bias in 53% (24/45) of the included studies was classified as low, according to the JBI Critical Appraisal tool [ 25 - 42 , 47 - 52 ]. In total, 18% (8/45) of the studies showed a moderate risk of bias [ 43 - 46 , 53 - 56 ]. Finally, 27% (12/45) of the included studies showed a high risk of bias [ 57 - 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of bias in 53% (24/45) of the included studies was classified as low, according to the JBI Critical Appraisal tool [ 25 - 42 , 47 - 52 ]. In total, 18% (8/45) of the studies showed a moderate risk of bias [ 43 - 46 , 53 - 56 ]. Finally, 27% (12/45) of the included studies showed a high risk of bias [ 57 - 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rzymski et al [29] believe that the easy availability and wide distribution of the Internet, forums and social media provide a fertile ground for the uncontrolled spread of false news and misinformation. Cardo, Kraus and Kaifie point to a wide range of misinformation that poses a global problem-from "denial, downplaying, or conspiracy theories to false and unsubstantiated claims regarding the origin of the virus and the inefficacy of cures and protective measures" [41] (p. 2). Some authors [42] even characterized the then President of the United States, Donald Trump, as the biggest initiator of false news about the coronavirus because he promoted dangerous and ineffective methods in the process of treatment and protection.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Germany identified demographic and political factors, with male left-wing voters who trust authorities, consume public media, and perceive COVID-19 as a significant health risk displaying the highest intention to vaccinate ( El-Far Cardo et al, 2021 ). Other studies of the Germany context establish links between vaccine hesitancy and conspiracy mindedness ( Jensen, Pfleger, et al, 2021 ) and between favorability of countries and foreign vaccines ( Jensen, Wagoner, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%